Autosomal dominant polycystic kidney disease: the changing face of clinical management. Issue 9981 (16th May 2015) - Ong, Albert C M; Devuyst, Olivier; Knebelmann, Bertrand; Walz, Gerd; ,
Summary: Autosomal dominant polycystic kidney disease is the most common inherited kidney disease and accounts for 7–10% of all patients on renal replacement therapy worldwide. Although first reported 500 years ago, this disorder is still regarded as untreatable and its pathogenesis is poorly understood despite much study. During the past 40 years, however, remarkable advances have transformed our understanding of how the disease develops and have led to rapid changes in diagnosis, prognosis, and treatment, especially during the past decade. This Review will summarise the key findings, highlight recent developments, and look ahead to the changes in clinical practice that will likely arise from the adoption of a new management framework for this major kidney disease.